Targeted chromosomal duplications and inversions in the human genome using zinc finger nucleases - Lee, Hyung Joo; Kweon, Jiyeon; Kim, Eunji; Kim, Seokjoong; Kim, Jin-Soo

(untitled) (Genome Research, 2012)
Despite the recent discoveries of and interest in numerous structural variations (SVs)—which include duplications and inversions—in the human and other higher eukaryotic genomes, little is known about the etiology and biology of these SVs, partly due to the lack of molecular tools with which to create individual SVs in cultured cells and model organisms. Here, we present a novel method of inducing duplications and inversions in a targeted manner without pre-manipulation of the genome. We found that zinc finger nucleases (ZFNs) designed to target two different sites in a human chromosome could introduce two concurrent double-strand breaks, whose repair via non-homologous end-joining (NHEJ) gives rise to targeted duplications and inversions of the genomic segments of up to a mega base pair (bp) in length between the two sites. Furthermore, we demonstrated that a ZFN pair could induce the inversion of a 140-kbp chromosomal segment that contains a portion of the blood coagulation factor VIII gene to mimic the inversion genotype that is associated with some cases of severe hemophilia A. This same ZFN pair could be used, in theory, to revert the inverted region to restore genomic integrity in these hemophilia A patients. We propose that ZFNs can be employed as molecular tools to study mechanisms of chromosomal rearrangements and to create SVs in a predetermined manner so as to study their biological roles. In addition, our method raises the possibility of correcting genetic defects caused by chromosomal rearrangements and holds new promise in gene and cell therapy.